2001
DOI: 10.1055/s-2001-12900
|View full text |Cite
|
Sign up to set email alerts
|

Genome Size and Pollen Viability as Taxonomic Criteria: Application to the Genus Hosta

Abstract: Genome size (C values) and pollen viability staining were applied as new criteria to investigate the taxonomy of the genus Hosta Tratt. (Hostaceae). Nearly all species of the genus Hosta have the same basic chromosome number (2n = 2x = 60). However, the nuclear DNA contents, as measured by flow cytometry with propidium iodide, could be demonstrated to range between 17.2 to 26.6 pg. This implies that the largest genome contains roughly 1010 more base pairs than the smallest. Therefore, nuclear DNA content is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 29 publications
5
75
1
Order By: Relevance
“…Where many species in a genus have the same chromosome numbers, differences in nuclear DNA content are often present and have proven to be very effective in delimiting infrageneric divisions in a number of taxa (Ohri 1998). Genome size has been demonstrated to often vary a factor 1.5-3 between taxa with identical chromosome numbers (Ohri 1998;Yokoya et al 2000;Zonneveld 2001;Zonneveld and van Iren 2001;Ellul et al 2002;Zonneveld et al 2003a, b;Hirsch et al 2004: Albach andGreilhuber 2004;Zonneveld and Duncan 2006). Moreover, Greilhuber (1998Greilhuber ( , 2005 has clearly shown that intraspecific variation of genome size is much less than assumed.…”
Section: Introductionmentioning
confidence: 99%
“…Where many species in a genus have the same chromosome numbers, differences in nuclear DNA content are often present and have proven to be very effective in delimiting infrageneric divisions in a number of taxa (Ohri 1998). Genome size has been demonstrated to often vary a factor 1.5-3 between taxa with identical chromosome numbers (Ohri 1998;Yokoya et al 2000;Zonneveld 2001;Zonneveld and van Iren 2001;Ellul et al 2002;Zonneveld et al 2003a, b;Hirsch et al 2004: Albach andGreilhuber 2004;Zonneveld and Duncan 2006). Moreover, Greilhuber (1998Greilhuber ( , 2005 has clearly shown that intraspecific variation of genome size is much less than assumed.…”
Section: Introductionmentioning
confidence: 99%
“…(Zonneveld & Van Iren, 2001), Galanthus L. (Zonneveld & al., 2003a), Agapanthus L'Hér. (Zonneveld & Duncan, 2003b), Nerine Herb (Zonneveld & Duncan, 2006), Narcissus L. (Zonneveld, 2008) and Tulipa L. has shown that nuclear DNA content of species and cultivars can contribute to the taxonomy of species and the origin of hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…The chopping was done with a new razor blade in a Petri dish in 0.25 ml nucleiisolation buffer to which 0.25 mg RNase/ml was added (Zonneveld and Van Iren 2001). After adding 1.75 ml propidium iodide solution (50 mg PI/l in isolation buffer), the suspension with nuclei was filtered through a 30-lm nylon filter.…”
Section: Flow Cytometric Measurement Of Dna 2c Valuementioning
confidence: 99%
“…Primitive angiosperms are now supposed to have had small genomes; increases up to a factor of 1,000 have occurred independently in various modern taxa (Leitch et al 1998). Flow cytometry was successfully used to measure the 2C-value for the genera Hosta Tratt., Helleborus L., Clivia Lindl., Nerine Herb., Agapanthus L'Hér., Galanthus L., Narcissus L., Gasteria Duval., Tulipa L., etc., by Zonneveld ( , 2008Zonneveld ( , 2009), Zonneveld and Van Iren (2001), Duncan (2003, 2006), Zonneveld and Van Jaarsveld (2005) and . In this paper it is shown that genome size alone is not sufficient to discriminate all species of Eucomis.…”
Section: Introductionmentioning
confidence: 99%